“Enseñar para renacer de las cenizas” Material didáctico con podcast para la enseñanza del conflicto armado, memoria histórica y paz en el Colegio Sergio Ariza, municipio de Sucre, departamento de Santander, para estudiantes de grado décimo y once. (2022)
The present work aims to contribute to the teaching on the armed conflict, historical memory and peace in the Sergio Ariza School of the municipality of Sucre in the department of Santander, this is achieved through a teaching material with podcast due to its type of language, which allows an innovative language and easy to understand. This work presents a series of categories, where different bibliographical sources are addressed to support the work. It begins with the identification of the need, here it is addressed from the personal to the regional and national in the issue of armed conflict historical memory and peace building, after which it begins with the exploration of the difficulty, in this part different sources are identified that deepen the specific aspects of each of these scales and are analyzed around the categories of armed conflict, historical memory and pedagogy of peace, then contextual and pedagogical realization is made, it explains the methodological design and the previous phases of the pedagogical proposal followed by this evaluation of the material is done in the Sergio Ariza College of the municipality of Sucre in the department of Santander, with tenth and eleventh grade students and to finish this sequence digital production is performed and a web page is obtained as a final product of this work.